Cognitive-behavior therapy - Persons, Jacqueline B.; Skrabak, Rosalie; Broderson, Gene; McNeil, Julia Frank; VandenBos, Gary R. (APA psychotherapy series. Systems of psychotherapy., 1994)
In Cognitive-behavior therapy, Jacqueline B. Persons demontrates this frequently used system of psychotherapy. Dr. Persons uses a case conceptualization as a guide for choosing which standard cognitive-behavioral interventions to apply, and she adopts an active approach to helping clients solve problems. In this session, Dr. Persons works with a 29-year old woman who recently developed social phobia. Together they work to overcome her fears through the use of exposure exercises and strategies for making social interactions more manageable. This DVD features a client portrayed by an actor on the basis of actual case material.